Enzyme responsive mesoporous silica nanoparticles for targeted tumor therapy in vitro and in vivo1. Issue 8 (28th February 2015) - Liu, Junjie; Zhang, Beilu; Luo, Zhong; Ding, Xingwei; Li, Jinghua; Dai, Liangliang; Zhou, Jun; Zhao, Xiaojing; Ye, Jingya; Cai, Kaiyong
<x xml:space="preserve">Abstract</x> A tumor microenvironment enzyme-responsive drug delivery system based on mesoporous silica nanoparticles is fabricated for targeted tumor therapy in vitro and in vivo.